Molten Bismuth–Bismuth/Zinc Oxide Composites for High-Temperature Thermal Energy Storage - Cristina Maria Vladut; Daniel Lincu; Daniela Berger; Cristian Matei; Raul-Augustin Mitran (Inorganics, 2024)
Thermal energy storage is at the leading edge of various applications, including waste heat recovery, solar storage and zero-energy buildings. Phase change materials (PCMs) can be utilized to store heat through reversible solid–liquid phase transitions. PCMs provide high energy storage capacity at a constant temperature. The volume change during the phase transition, on the other hand, causes inconsistency in crystallization and leakage, increasing the system’s complexity and shortening the lifetime of these materials. These shortcomings can be diminished by impregnation in a porous matrix or encapsulation with an inert shell, resulting in shape-stabilized PCMs that maintain their macroscopic shape during phase change. The synthesis and properties of Bi/ZnO nanocomposites were investigated in order to obtain shape-stabilized phase change materials. All samples consisted of metallic Bi and oxide, doped with 1–3% at. zinc. Heat storage capacities between 31 and 49 Jg−1 were obtained, depending on the mass fraction of the metal. All samples had good thermal reliability, retaining their heat storage properties after 50 consecutive heating–cooling cycles. An average oxide layer thickness of 75–100 nm is sufficient to prevent the molten metal leakage at temperatures above its melting point, resulting in shape-stabilized PCMs.